An Analysis of the Meaning of Divorce Lawsuits by High-Income Women at the Sidoarjo Religious Court - Isdiany, Amelinda Devina; Sudrajat, Arief (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
The increase in the number of divorce cases filed by high-income women indicates a significant change in gender relations and the meaning of marriage in modern society. This phenomenon is clearly evident in the Sidoarjo Religious Court, where the majority of divorce cases are filed by wives who are economically independent. This study aims to analyze the factors causing divorce and its meaning for high-income women in social, legal, and gender contexts. This study uses a qualitative method with a case study approach. Data collection was conducted through in depth interviews, observation, and documentation of women filing for divorce at the Sidoarjo Religious Court. Data analysis was conducted descriptively using George Herbert Mead's symbolic interactionism theory to understand divorce lawsuits as social actions shaped through interaction and meaning making processes. The results show that divorce lawsuits are influenced by accumulated domestic conflicts, gender inequality, verbal abuse, infidelity, and the husband's failure to fulfill material and emotional obligations. Economic independence gives women a stronger bargaining position to evaluate and end marriages that are considered unfair. Divorce suits are interpreted as a form of agency, symbolic resistance to unequal relationships, and an effort to maintain dignity and personal well being.